2004
DOI: 10.1080/1521-6540400000850
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Oxidative Response of Carbonic Anhydrase III in Skeletal Muscle

Abstract: SummaryWe propose that carbonic anhydrase III (CAIII) functions as an anti-oxidant agent in skeletal muscle. To explore this hypothesis, we analyzed the gene expression profile of skeletal muscle in mice deficient in CAIII gene utilizing the murine genome U74Av2 set microarray. Pairwise comparison between CAIII knockout mice and their wild-type littermates revealed that more than 500 of 12,000 genes in the array showed an altered level of transcription. Of particular note were transcriptional alterations among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…S-glutathionylation of proteins is an early response to oxidative damage [77]. S-glutathionylation of Car3 increases with increased oxidative damage that occurs naturally as in aging [78] or with muscle damage [22]. Car3 contains numerous other additional cysteine residues not found in Car1/2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S-glutathionylation of proteins is an early response to oxidative damage [77]. S-glutathionylation of Car3 increases with increased oxidative damage that occurs naturally as in aging [78] or with muscle damage [22]. Car3 contains numerous other additional cysteine residues not found in Car1/2.…”
Section: Discussionmentioning
confidence: 99%
“…However, CA III does differ in amino acid alignment with the closely related CA I and CA II proteins at two important residues, as depicted in (Fig 1), lysine 64 (Lys) and phenylalanine 198 (Phe), which dramatically decrease the activity of CA III [13–17]. While the function of CA III is currently unknown it has been speculated to be involved in metabolism, oxidative damage response, and mitochondrial ATP synthesis [1822]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonic anhydrase III is expressed predominantly in skeletal muscle and has been suggested to be an indicator of muscle damage [39]. It has been proposed that this protein functions as an essential anti-oxidant agent in skeletal muscle [40]. Decreased levels of carbonic anhydrase III in the myalgic muscle may indicate an imbalance in the cellular redox potential in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…CA III is a cytosolic enzyme highly expressed in skeletal muscle in rats. It was demonstrated that in skeletal muscle, CA III also exhibits a protective role against peroxide (Zimmerman et al 2004). Thus, the complex I integrated CAs could protect tissues against peroxides when its normal expression is high.…”
Section: Predicted Physiological Role Of Atccasmentioning
confidence: 97%